EXPLORING THE IMPACT OF ESG DISCLOSURE, DIVIDEND PAYOUT RATIO, AND INSTITUTIONAL OWNERSHIP ON FIRM VALUE: A MODERATED ANALYSIS OF FIRM SIZE - Dihardjo, Jason Ferdianto; Hersugondo, Hersugondo (Fakultas Ekonomi dan Bisnis, UNTAN, 2023)
This study explores the effect of environmental, social, and governance (ESG) disclosure, dividend payout ratio (DPR), and institutional ownership on firm value in Indonesia during the period of 2010